Seed Germination in Red Mud: Roles of Plant Traits and Metal Availability - Jian-Rui Wang; Jian-Xiong Liao; Qian-Wen Jiang; Ling Mo; Rui-Xia Ma; Jing-Jing Feng (Water, Air, & Soil Pollution, 2026)

Integrating aquatic crops into rotation systems enhances soil health and suppresses potential fungal pathogens in greenhouse cucumber production - Jun Xu; Zhuoya Zhao; Liu Pan; Yuan Yao; Zhi Li; Yurui Wang; Yanfeng Li; Xuehao Chen (Applied Soil Ecology, 2026)

Elucidation of Baicalein’s Anti-Intervertebral Disc Degeneration Mechanism Through Network Pharmacology and Experimental Validation - Rui Wang; Zhiyong Liu; Xiaopeng Zhao (Cell Biochemistry and Biophysics, 2026)
This study aims to elucidate the biological effects of Baicalein (BA) on intervertebral disc degeneration (IDD) and the potential mechanisms involved. Network pharmacology analysis was performed to identify the core targets and signaling pathways responsible for the therapeutic effects of BA on IDD. In vitro validation was carried out using IL-1β-stimulated nucleus pulposus cells (NPCs). Cell viability, apoptosis, inflammatory cytokines (TNF-α, IL-6), extracellular matrix (ECM)-related molecules (MMP3, Aggrecan, Collagen II), and the phosphorylation of ERK and p38 were measured using CCK-8 assay, flow cytometry, qRT-PCR, ELISA and Western blot. Network pharmacology identified 80 common targets and highlighted the MAPK signaling pathway as a key mechanism. In vitro, BA (50 µmol/L) mitigated IL-1β-induced cytotoxicity in NPCs and promoted cell proliferation. BA significantly inhibited apoptosis by regulating the Bcl-2/Bax family and cleaved c-caspase-3. It also decreased the expression of TNF-α and IL-6, and reversed ECM homeostasis by modulating MMP-3, Aggrecan and Collagen II expression. Furthermore, BA treatment effectively suppressed IL-1β-induced phosphorylation of ERK and p38. Notably, the MAPK agonist anisomycin partially abolished the above protective phenotypes of BA and restored MAPK phosphorylation. BA alleviates apoptosis, inflammatory response and ECM degradation in NPCs, to retard IDD development mainly through inhibiting MAPK pathway activation, supporting the clinical translational potential of BA for IDD treatment.

A Novel Evidence of Consistency Between the Upper and Lower Airways in Central Regulation - Hanrui Wang; Xiaoyu Song; Ting Yang; Hui Shen; Tongpeng Chu; Yakui Mou; Chao Ren; Xicheng Song (Neuroscience Bulletin, 2026)

Higher nutrient availability fosters intricate bacterial networks in rhizosphere of invasive plants - Mengxin Zhao; Han Zhang; Qiao Li; Die Zhang; Jianying Guo; Rui Wang; Fengjuan Zhang; Fanghao Wan; Wanxue Liu (Applied Soil Ecology, 2026)

Intercropping enhances aggregate stability on acidic red-soil slopes via an arbuscular mycorrhizal fungi-mediated glomalin-enzyme pathway - Ruolan Tang; Qirui Wang; Huahui Li; Xiongxing Pu; Wanting Li; Benshuai Yan; Ting Wang; Zilin Wang; Maopan Fang; Xinyue Li; Yongmei Li; Jixia Zhao (Applied Soil Ecology, 2026)

Nitrogen fertilization shapes rhizosphere microbiome to boost peanut yield: A two-year field study - Xiangjun Kong; Peipei Jia; Lijie Li; Ali Muhammad; Rui Wang; Aziz Khan; Jaya Nepal; Fei Li; Zhiyong Zhang (Applied Soil Ecology, 2026)

Impacts of green manure rotations and alkaline amendments on soil health and assembly and function of bacterial communities - Jinchang Liang; Heli Shi; Bikun Xiang; Luping Chi; Rui Wang; Guangwei Sun; Yuxiao Sun; Jing Wang; Jun Tan; Xiaoqiang Wang (Applied Soil Ecology, 2025)

A stochastic modeling framework for radionuclide migration from deep geological repositories considering spatial variability - Zhibao Zheng; Xuerui Wang; Judith Flügge; Thomas Nagel (Advances in Water Resources, 2025)

Micro-scale experimental investigation of the effect of pore space deformation on trapping of supercritical CO2 - Rui Wang; Maziar Arshadi; Mohammad Piri (Advances in Water Resources, 2023)